Bystander activation in memory and antigen-inexperienced memory-like CD8 T cells - Paprckova, Darina; Salyova, Eva; Michalik, Juraj; Stepanek, Ondrej (Current opinion in immunology, 2023)
Antigen-induced memory T cells undergo counterintuitive activation in an antigen-independent manner, which is called bystander response. Although it is well documented that memory CD8+ T cells produce IFNγ and upregulate the cytotoxic program upon the stimulation with inflammatory cytokines, there is only rare evidence that this provides an actual protection against pathogens in immunocompetent individuals. One of the reasons might be numerous antigen-inexperienced memory-like T cells that are also capable of the bystander response. Little is known about the bystander protection of memory and memory-like T cells and their redundancies with innate-like lymphocytes in humans because of the interspecies differences and the lack of controlled experiments. However, it has been proposed that IL-15/NKG2D-driven bystander activation of memory T cells drives protection or immunopathology in particular human diseases.
Keywords: CD8-Positive T-Lymphocytes; Lymphocyte Activation; cytokiny; imunologická paměť; CD8-pozitivní T-lymfocyty; Cytokines; Immunologic Memory; antigeny; lidé; Humans; aktivace lymfocytů; Antigens